2020
DOI: 10.3389/fnmol.2020.00134
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Microglia From Alzheimer’s Disease Donors and Non-demented Elderly in Acute Human Postmortem Cortical Tissue

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 52 publications
4
64
0
Order By: Relevance
“…TREM2 upregulation had also been determined in peripheral mononuclear cells from AD patients and mild cognitive impairment [52,53], implicating that the TREM2 upregulation may be a systemic response of myeloid cells with the progression of AD. The snRNAseq data on individual AD postmortem sample and AD mouse model also revealed that TREM2/Trem2 was upregulated in AD pathology and AD-related conditions ( Figure 1D,E) [45,[54][55][56][57]. In addition, Trem2 is also upregulated in an amyloidosis progression-related pattern, predominantly in plaquesurrounding microglia [58].…”
Section: Trem2 and Disease-associated Microglia (Dam)mentioning
confidence: 80%
See 1 more Smart Citation
“…TREM2 upregulation had also been determined in peripheral mononuclear cells from AD patients and mild cognitive impairment [52,53], implicating that the TREM2 upregulation may be a systemic response of myeloid cells with the progression of AD. The snRNAseq data on individual AD postmortem sample and AD mouse model also revealed that TREM2/Trem2 was upregulated in AD pathology and AD-related conditions ( Figure 1D,E) [45,[54][55][56][57]. In addition, Trem2 is also upregulated in an amyloidosis progression-related pattern, predominantly in plaquesurrounding microglia [58].…”
Section: Trem2 and Disease-associated Microglia (Dam)mentioning
confidence: 80%
“…In addition, such disparities may also remind us to pay attention to the dose effect of Trem2 as well as the interaction of Trem2 with other inflammatory pathways. Noteworthy, it should be mindful that mouse models may not comprehensively recapitulate microglial changes in AD patients based on the inconsistent microglial transcriptomics profiling between AD mouse models and AD [54,56,81,82]. Therefore, further patients-based studies may help to determine the roles of TREM2 in shaping microglial phenotypes and DAM functions in AD.…”
Section: Ank Hif1a Tgfb1mentioning
confidence: 99%
“…Given the difficulty in capturing microglia and endothelial cells using snRNA-seq [ 54 ], additional transcriptomic investigations of these cells in the white matter of CTE are warranted, especially in light of previous studies showing increases in neuroinflammatory microglia in DLF cortex in CTE [ 11 13 ]. Future studies isolating microglia, neurons, and endothelial cells for in depth transcript profiling are also warranted [ 3 , 51 ]. Furthermore, additional studies specifically isolating astrocyte nuclei for sequencing will enhance the findings presented here [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with astrocytes, the APOE expression in microglia is upregulated in AD patients (Mathys et al, 2019). The upregulation of APOE in microglia can result from either a disrupted regulation specifically in microglia or a disease-associated subpopulation, although recent studies have not detected an AD-specific subpopulation in microglia in the cortex of AD patients (Alsema et al, 2020;Mathys et al, 2019). More studies are needed to examine this regulatory effect of the APOE ε4 variant at the cell level, including microglia.…”
Section: Discussionmentioning
confidence: 99%